Les aqueducs de Gaule romaine de l’Antiquité tardive, entre construction, restauration et abandon - Borau, Laëtitia; Alix, Stéphane (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2021)
Abstract Few studies are dedicated to the aqueducts of Roman Gaul during Late Antiquity. The objective here is to explore the situation of the water supply network, mainly those of capitals of cities, from the transition phase of the 3rd century, and based on the examination of representative sites such as Lyon, Bordeaux, Périgueux, Reims, Narbonne or Nîmes. Several situations are thus intended: the abandonment of aqueducts from Late Antiquity, the keeping of these canalisations through regular maintenance, occasional restorations or partial reconstructions, or even new constructions. The study of the insertion of these water networks in the urban grid as well as their relationship with the related structures such as water pipes, fountains or thermal baths provides essential information to understand the continuity of the aqueducts. Far from being exhaustive, this research lays the basis for an analysis that deserves to be much more in-depth, as evidenced by the diversity and richness of the presented case studies. Contrary to a generally widespread idea, it shows that water supply networks seem to have been maintained, in different circumstances from one city to another, at least during part of Late Antiquity in the different provinces of Roman Gaul.